2021
DOI: 10.1021/acs.inorgchem.1c02147
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Driven Self-Assembly of Lanthanide Bis-phthalocyaninates into Conductive Quasi-MOF Nanowires: an Approach toward Easily Recyclable Organic Electronics

Abstract: Controlled self-assembly and rapid disintegration of supramolecular nanowires is potentially useful for ecology-friendly organic electronics. Herein, a novel method exploiting the binding between crown-substituted double-decker lanthanide phthalocyaninates (ML2, M = Lu, Ce, Tb) and K+ ions is applied for the one-step fabrication of macroscopically long conductive one-dimensional quasi-metal–organic frameworks. Their properties are controlled by the size of the lanthanide ion guiding the assembly through either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
(104 reference statements)
0
13
0
Order By: Relevance
“…39a). 451 Noteworthy, this possibility was envisaged in 1994 by Toupance et al in one of keystone papers on the construction of ionoelectronic materials based on crown-substituted phthalocyanines; however, experimental verification of this hypothesis was reported only in 2021.…”
Section: Supramolecular Assembling Of Semiconductive Materials Based ...mentioning
confidence: 99%
“…39a). 451 Noteworthy, this possibility was envisaged in 1994 by Toupance et al in one of keystone papers on the construction of ionoelectronic materials based on crown-substituted phthalocyanines; however, experimental verification of this hypothesis was reported only in 2021.…”
Section: Supramolecular Assembling Of Semiconductive Materials Based ...mentioning
confidence: 99%
“…In summary, it has been demonstrated that the large radius of the Gd(III) ion determines the intramolecular incorporation of potassium cations into the double-decker crown-substituted phthalocyaninate, in contrast to the Lu(III) double-decker. 62,65 Furthermore, we achieved the supramolecular controlled ligand reduction of the double-decker Gd phthalocyaninate and the formation of the reduced inclusion complex {Gd-[(15C5) 4 Pc 2−/2− ] 2 − •4K + } 3+ . The increased distance between the ligands due to the supramolecular inclusion of potassium cations facilitates the switching of the redox state of the phthalocyanine.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…62,63,65 leads to a very high electron conductivity of the final material up to 11.4 S•cm −1 . 65 In contrast, a similar strategy for the middle lanthanides results in an electron conductivity that is 8 orders of magnitude lower. The reason for this difference has not been studied in detail, but our work reveals an important factor for that.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of this protein as a drug is still an extremely common procedure in improving the quality of life for patients with diabetes. The questions of searching for chromatographic methods for specific isolation and determination are still important. Thin-film materials containing lanthanide atoms, as an example of nanotechnology, are actively used in many fields. Also, materials containing lanthanide atoms are being actively studied as materials for bioorganic sensors, including for determining the activity of insulin and analytical applications in the analysis of insulin content in complex systems. , Taking into account all of the problems associated with the production and application of such materials for proteomics, the purpose of this work is to demonstrate the possibility of using films containing lanthanide ions for insulin adsorption.…”
Section: Introductionmentioning
confidence: 99%